(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The paper proposes a new CMMI-based risk management framework for lean implementation. Any process improvement framework implementation is subject to many unknowns and uncertainties. Generally new process improvement framework starts with certain assumptions, dependencies, and limitations, which may convert into a potential problem or risks. Those risks need to be managed in a systematic and structured way. Lean is one of the most widely used process improvement framework across the industry and in varied domains & spheres of the organisation. Mining organizations are also implementing lean but with a very limited benefits and success. The successful and rewarding lean implementation has been a big challenge for the process improvement experts & lean practitioners. It requires a robust risk management strategy to mitigate unforeseen events and potential issues. The paper proposes CMMI’s Risk Management-based framework for managing the risks during lean implementation. It will propose multiple levels of process areas & practices. The framework will be based on the multiple levels of capability / maturity rating system as defined in CMMI V1.3. There are some limitations of using the framework and its should be customized as per the organizational requirements. Also, further enhancement can be done by adding more tools, techniques and practices, which will make it more robust.